Two new species of Cyrtodactylus (Squamata: Gekkonidae) from the Southern Bukit Barisan Range of Sumatra and an estimation of their phylogeny - Harvey, Michael B.; O’connell, Kyle A.; Barraza, Gabriel; Riyanto, Awal; Kurniawan, Nia; Smith, Eric N. (Zootaxa, 2015)
We describe Cyrtodactylus psarops sp. nov. and C. semicinctus sp. nov., two new species of bent-toed geckos from montane forests in the southern Bukit Barisan Range of Sumatra, Indonesia. The new species are closely related to one another and to C. semenanjungensis, a lowland species currently known only from Peninsular Malaysia. Three characters of the new species immediately distinguish them from most congeners in the Sunda Region: they lack transversely enlarged subcaudals, have a precloacal depression, and have a greatly enlarged scale positioned at the apex of a continuous series of femoral and precloacal pore-bearing scales. They differ from one another in cephalic pattern, tuberculation of the brachium, and in numbers of cloacal tubercles, dorsal bands, and ventrals in a transverse row. The greatly enlarged scale at the apex of the precloacal pores appears to be a rare apomorphy of these two species and C. agamensis.